Contesting neoliberal knowledge politics in restoration governance: the restorationist's dilemma. Issue 3 (3rd May 2020) - Rozance, Mary Ann; Denham, Diana; Kidd, Sarah
ABSTRACT: The success of ecological restoration efforts is tightly coupled with the effectiveness of many U.S. environmental policies. Yet scholars have raised questions about the ability of restoration to produce intended results. We use a case study of tidal wetland restoration planning in Oregon to examine how neoliberal environmental governance exercises influence through a set of knowledge politics that produces subpar outcomes. We present three main findings: (1) restoration policies produce a restoration economy based on a conception of wetland as commodity (2) practitioners in this restoration economy exhibit competitive behavior resulting in a piecemeal rather than a landscape approach to restoration; and (3) limited monitoring prevents changes to existing policies. Practitioners offer insight into the challenge of treating wetlands as a commodity and call for more monitoring to challenge the assumptions of hegemonic knowledge practices that reinforce a neoliberal environmental governance regime. The divergent ideas of reflexive practitioners, though not yet manifest as action, show where changes to restoration governance might be possible.